Parental smoking and children's respiratory health: independent effects of prenatal and postnatal exposure. (2nd August 2006) - Pattenden, Sam; Antova, Temenuga; Neuberger, Manfred; Nikiforov, Bojidar; De Sario, Manuela; Grize, Leticia; Heinrich, Joachim; Hruba, Frantiska; Janssen, Nicole; Luttmann-Gibson, Heike; Privalova, Larissa; Rudnai, Peter; et al.
Abstract : Objectives: Adverse effects have been reported of prenatal and/or postnatal passive exposure to smoking on children's health. Uncertainties remain about the relative importance of smoking at different periods in the child's life. We investigate this in a pooled analysis, on 53 879 children from 12 cross-sectional studies—components of the PATY study (Pollution And The Young). Methods: Effects were estimated, within each study, of three exposures: mother smoked during pregnancy, parental smoking in the first two years, current parental smoking. Outcomes were: wheeze, asthma, "woken by wheeze", bronchitis, nocturnal cough, morning cough, "sensitivity to inhaled allergens" and hay fever. Logistic regressions were used, controlling for individual risk factors and study area. Heterogeneity between study-specific results, and mean effects (allowing for heterogeneity) were estimated using meta-analytical tools. Results: There was strong evidence linking parental smoking to wheeze, asthma, bronchitis and nocturnal cough, with mean odds ratios all around 1.15, with independent effects of prenatal and postnatal exposures for most associations. Conclusions: Adverse effects of both pre- and postnatal parental smoking on children's respiratory health were confirmed. Asthma was most strongly associated with maternal smoking during pregnancy, but postnatal exposure showed independent associations with a range of other respiratory symptoms. All tobacco smoke exposure has serious consequences for children's respiratory health and needs to be reduced urgently.